2016
DOI: 10.1039/c6cc01045h
|View full text |Cite
|
Sign up to set email alerts
|

A methylation-switchable conformational probe for the sensitive and selective detection of RNA demethylase activity

Abstract: We describe a novel methylation-sensitive nucleic acid (RNA) probe which switches conformation according to its methylation status. When combined with a differential scanning fluorimetry technique, it enables highly sensitive and selective detection of demethylase activity at a single methylated-base level. The approach is highly versatile and may be adapted to a broad range of RNA demethylases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 34 publications
0
28
0
Order By: Relevance
“…We were also able to demonstrate that the thermal tags had little impact on the catalytic activities of AlkB demethylases. Notably, ALKBH5 and FTO preferentially demethylate N 6 ‐methyladenosine (m 6 A) substrates, whereas ALKBH3 favors N 1 ‐methyladenosine (m 1 A) substrates . Consistent with their inherent substrate specificity, detailed kinetic analyses revealed that ALKBH5 and FTO modified with either KE or RD tags displayed similar affinities ( K m ) and catalytic efficiencies ( k cat / K m ) for the m 6 A substrate as that of their unmodified proteins (Figure G and H and Figure S2 in the Supporting Information), whereas ALKBH3 conjugated with either KE or RD tags retained >90 % of its canonical demethylase activity against the m 1 A substrate (Figure I and Figure S2 I in the Supporting Information).…”
Section: Effect Of Thermal Tags On the Catalytic Activity Of The Alkbmentioning
confidence: 99%
See 2 more Smart Citations
“…We were also able to demonstrate that the thermal tags had little impact on the catalytic activities of AlkB demethylases. Notably, ALKBH5 and FTO preferentially demethylate N 6 ‐methyladenosine (m 6 A) substrates, whereas ALKBH3 favors N 1 ‐methyladenosine (m 1 A) substrates . Consistent with their inherent substrate specificity, detailed kinetic analyses revealed that ALKBH5 and FTO modified with either KE or RD tags displayed similar affinities ( K m ) and catalytic efficiencies ( k cat / K m ) for the m 6 A substrate as that of their unmodified proteins (Figure G and H and Figure S2 in the Supporting Information), whereas ALKBH3 conjugated with either KE or RD tags retained >90 % of its canonical demethylase activity against the m 1 A substrate (Figure I and Figure S2 I in the Supporting Information).…”
Section: Effect Of Thermal Tags On the Catalytic Activity Of The Alkbmentioning
confidence: 99%
“…Notably,A LKBH5 and FTO preferentially demethylate N 6 -methyladenosine (m 6 A) substrates, whereas ALKBH3 favors N 1 -methyladenosine (m 1 A) substrates. [55,56] Consistent with their inher- ent substrate specificity,d etailed kinetic analyses revealed that ALKBH5 and FTO modified with either KE or RD tags displayed similar affinities( K m )a nd catalytic efficiencies (k cat /K m )f or the m 6 As ubstrate as that of their unmodified proteins ( Figure 2G and Ha nd Figure S2 in the Supporting Information),w hereas ALKBH3 conjugated with either KE or RD tags retained > 90 % of its canonical demethylase activity against the m 1 As ubstrate ( Figure 2I and Figure S2 Ii nt he Supporting Information). This finding is interesting because, contrary to our results, ap revious study showed that the attachment of larger zwitterionic peptides, such as poly(Glu-Lys) 10 and 30 KDa in length, led to as ignificant increase in the substrate affinities of b-lactamases.…”
Section: Effect Of Thermal Tags On the Catalytic Activity Of The Alkbmentioning
confidence: 99%
See 1 more Smart Citation
“…Alkbh5 belongs to the nonheme Fe 2þ -and a-ketoglutarate (aKG)-dependent AlkB dioxygenases and catalyzes oxidative demethylation of single-stranded RNAs (4). Although several different methyl modifications have been described and cataloged in nucleic acids (5), Alkbh5 specifically demethylates N 6 -methyladenosine (m 6 A), with little to no activity for other methylated nucleotides (6,7). m 6 A is the most abundant internal modification of eukaryotic mRNA and long-noncoding RNA (8).…”
Section: Introductionmentioning
confidence: 99%
“…We validated the ability of probe 13 to assay ALKBH2 inhibitors by measuring the IC 50 of pyridine 2,4-dicarboxylic acid (PDCA), a broad-spectrum inhibitor of 2-OG-dependent enzymes [16] (Figure 3). The assay was conducted in a 60 µL reaction volume on a 384-well plate, yielding an IC 50 of 2.43 ± 0.12 µ m , fully consistent with reported values.…”
mentioning
confidence: 99%